MODEL OF SUSTAINABLE ENVIRONMENTAL MANAGEMENT IN STAR RATED HOTELS IN BALI - Jaya Pramono; Agung Suryawan Wiranatha; I Ketut Budi Susrusa (Centre For Tourism Planning and Development, 2014)
Maintaining environmental sustainability has become the main agenda in today's world, and so as in hotel industry. In Bali, the number of hotels has been increasing significantly. This growth positively correlates with the use of resources to meet the demand of tourists and the environmental damage, on the other hand. Therefore, the issue of environmentally friendly operation is getting prominent in star rated hotels in Bali.The aim of this research was to find out the relationships between the processes and the benefits of environmental management in star rated hotels in Bali. The important aspects of environmental management was covered in this research, namely: 1) Process of environmental management that consists of energy management, water management, wastewater and solid waste management, chemical waste management, and purchasing products for hotel operations; and 2) The benefits of the environmental management that consists of financial benefits, employee satisfaction, guest satisfaction, and the advantages from promotion and publicity. This research collecting data from 126 star rated hotels around Bali, and the data was analyzed by using SEM (Structural Equation Modeling).The model of environmental management in this research shows that the process of environmental management significantly influence the benefits of environmental management.